Pokémon. The Arceus chronicles [videorecording (DVD)] - Tajiri, Satoshi, 1965-; Masuda, Junichi, 1968-; Sugimori, Ken, 1966- (VIZ Media, 2024)
In this animated adventure, our heroes head to Sinnoh to learn about the region's past. After receiving a mysterious message from the Mythical Pokémon Arceus, they meet up with Brock, and the group heads to Mount Coronet to investigate. There, they find a rampaging Heatran and the commanders of Team Galactic, who are determined to find their missing leader by opening a gate between dimensions. Joined by a trio of Legendary Pokémon and Sinnoh Champion Cynthia, our heroes must give it their all to stop Sinnoh from being destroyed!